Efektivitas Media Phet Simulation Untuk Meningkatkan Hasil Belajar Peserta Didik - Rahmah, Ajeng Anisatu; Karlimah, Karlimah; Apriyani, Ika Fitri (Jurnal Ilmiah Wahana Pendidikan, 2024)
Learning media certainly affects the continuity of the teaching and learning process. This study aims to conduct a literature review related to the effectiveness of phet simulation media in learning mathematics in elementary schools. The research method chosen in this study is the Systematic Literature Review method. Data collection was carried out by presenting all articles which were similar studies in this study. The articles used in this study were 10 articles obtained from Google Scholar. Based on this research, it was found that phet simulation media in mathematics learning can improve the continuity of the teaching and learning process which is characterized by increased ability of students' learning outcomes. Based on a literature review conducted by phet simulation media, it can be developed in learning mathematics in elementary/